Clinical and biochemical presentation of childhood nephrotic syndrome: a comparative study of first episode and first relapse - Verma, Suresh K.; Goyal, Vishnu K.; Lora, Sawai S.; Raheja, Kapil; Dabi, Jagdish; Agarwal, Mudit (International Journal of Contemporary Pediatrics, 2017)
Background: Relapse of nephrotic syndrome occurs in 60-70% of initial responders. Relapse episodes may increase the morbidity and mortality in these patients. This study was planned to compare clinical presentation and biochemical derangements between first episode and first relapse of nephrotic syndrome. Methods: All children 1-18 years of age group, admitted with either first episode or first relapse nephrotic syndrome were included in this cross-sectional study, conducted in a teaching hospital. Besides detailed clinical examination, all the children were subjected to renal function tests, lipid profile, hemogram, CRP test and urine examinations. Results: Total 41 children (58.53% fresh and 41.46% relapse cases) qualified to be included in the study. Decreased urine output was more prevalent in first episode group (100% vs. 70.58%, p<0.05), and cough was more common in relapse group (52.94% vs.16.67%, p<0.05). In relapse group 35.29% had raised urea (more than 40mg/dl) and 23.52% had raised creatinine (more than 1 mg/dl) in comparison to none in first episode (p<0.05). Serum cholesterol more than 400mg/dl was more prevalent in relapse group in comparison to first episode (52.94% vs. 20.83% respectively, p-0.047). Conclusions: Cough is more prevalent in relapse group in comparison to first episode of nephrotic syndrome. Similarly, degree of rise of serum cholesterol and derangements of renal functions are more in relapse group.